Price Changes of Essential Food Commodities in Traditional Markets - Ayu Apprrilliani Selvia; Aisyah Dita Ariani; Wahyu Febri Ramadhan Sudirman (General Multidisciplinary Research Journal, 2026)
Introduction:The rapid advancement of information technology has accelerated the digital transformation of Indonesia’s financial sector, particularly in capital market investment activities. The emergence of digital investment platforms, online brokerage services, and financial technology applications has increased retail investor participation by improving accessibility, efficiency, and affordability. Methods:This study employed a qualitative literature review approach. Relevant studies were identified through searches in Scopus, ScienceDirect, and Google Scholar using the keywords digital investment, capital market, financial technology, online trading, retail investors, and Indonesia. The review included peer-reviewed journal articles published between 2020 and 2025. Inclusion criteria comprised studies focusing on digital investment adoption, investor behavior, financial technology, and capital market development, while duplicate articles, conference abstracts, editorials, and studies unrelated to investment activities were excluded. Following the screening process, 30 eligible articles were selected and analyzed using descriptive thematic analysis to identify recurring themes, opportunities, challenges, and research gaps. Results:The findings indicate that digital investment has significantly increased retail investor participation, improved market accessibility, enhanced trading efficiency, and supported financial inclusion in Indonesia. Nevertheless, the rapid expansion of digital investment has also heightened cybersecurity risks, information asymmetry, behavioral biases, and speculative investment practices that may influence investment decisions and market stability. Conclusion and Suggestion:Digital investment has become an important driver of Indonesia’s capital market development. However, sustainable growth requires strengthening financial literacy, enhancing investor protection, improving cybersecurity measures, and implementing adaptive regulatory frameworks. Future studies are recommended to employ empirical methods to examine the causal relationships between digital investment adoption, investor behavior, financial literacy, and capital market performance in Indonesia.